A helmetless-tackling intervention in American football for decreasing head impact exposure: A randomized controlled trial. Issue 10 (October 2019) - Swartz, Erik E.; Myers, Jay L.; Cook, Summer B.; Guskiewicz, Kevin M.; Ferrara, Michael S.; Cantu, Robert C.; Chang, Hong; Broglio, Steven P.
Abstract: Objectives: To evaluate a behavioral intervention to reduce head impact exposure in youth playing American football. Design: Nested randomized controlled trial. Methods: Participants, ages 14–17 years, wore head impact sensors (SIM-G™) during two seasons of play. Those randomized to the intervention group underwent weekly tackling/blocking drills performed without helmets (WoH) and shoulder pads while the control group trained as normal, matching frequency and duration. Research personnel provided daily oversight to maintain fidelity. Head impact frequency (≥10 g) per athlete exposure (ImpAE) was analyzed over time (two 11-week seasons) using mixed effect models or ANCOVA. Secondary outcomes included exposure-type (training, game) and participation level (entry-level versus upper-level secondary education). Results: One-hundred fifteen participants (59 WoH, 56 control) met compliance criteria, contributing 47, 382 head impacts and 10, 751 athlete exposures for analysis. WoH had fewer ImpAE during games compared to control participants at weeks 4 (p = 0.0001 season 1, p = 0.0005 season 2) and 7 (p = 0.0001 both seasons). Upper-level WoH participants had less ImpAE during games than their matched controls at weeks 4 (p = 0.017 and p = 0.026) and 7 (p = 0.037 and p = 0.014) in both seasons, respectively. Upper-level WoH also had fewer ImpAE during training at week 7 (p = 0.015) in season one. Conclusions: Tackling and blocking drills performed without a helmet during training reduced the frequency of head impacts during play, especially during games. However, these differences disappeared by the end of the season. Future research should explore the frequency of behavioral intervention and a dose-response relationship considering years of player experience. Trial registration: ClinicalTrials.gov # NCT02519478.